2022
DOI: 10.3389/fcell.2022.941914
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Alleviates Acute Lung Injury by Regulating Neutrophil Motility and Neutrophil Extracellular Trap Formation

Abstract: Sepsis is predominantly initiated by bacterial infection and can cause systemic inflammation, which frequently leads to rapid death of the patient. However, this acute systemic inflammatory response requires further investigation from the perspectives of clinical judgment criteria and early treatment strategies for the relief of symptoms. Lysophosphatidylcholine (LPC) 18:0 may relieve septic symptoms, but the relevant mechanism is not clearly understood. Therefore, we aimed to assess the effectiveness of LPC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…However, the effect of LysoPC molecules on inflammation remains controversial. Both proinflammatory [23,25] and anti-inflammatory [26][27][28][29][30][31][32] effects of the LysoPC molecules have been reported previously. Our results are in agreement with other studies showing that LysoPC levels are lower in patients with more severe COVID-19 [26,28,29].…”
Section: Discussionmentioning
confidence: 58%
“…However, the effect of LysoPC molecules on inflammation remains controversial. Both proinflammatory [23,25] and anti-inflammatory [26][27][28][29][30][31][32] effects of the LysoPC molecules have been reported previously. Our results are in agreement with other studies showing that LysoPC levels are lower in patients with more severe COVID-19 [26,28,29].…”
Section: Discussionmentioning
confidence: 58%
“…34 LysoPC (18 : 0) can reduce inflammation by decreasing pro-inflammatory cytokines and increasing anti-inflammatory cytokines. 35,36 Specifically, we found that Parasutterella and Akkermansia were positively associated with LysoPE (18 : 0/ 0 : 0), LysoPC (20 : 3(5Z,8Z,11Z)), LysoPC (20 : 1(11Z)), LysoPC (20 : 2(11Z,14Z)) and LysoPC (P-18:0). Therefore, we hypothesized that A. muciniphila activates organismal immunity by increasing the abundance of Parasutterella and Akkermansia, thus affecting the metabolism of lipid and lipid-like molecules associated with LysoPCs and LysoPE, which is beneficial for the relief of colitis in mice.…”
Section: Papermentioning
confidence: 70%
“…First, lysophosphatidylcholines can increase neutrophil adhesion, increase the expression of the CD11b adhesion molecule expression and increase the expression of pro-chemotactic receptors for formylated peptides [ 24 ]; local neutrophil infiltration is thereby increased [ 25 ]. These metabolites also have the potential to increase neutrophil degranulation [ 24 ], increase neutrophil bactericidal activity [ 26 ], and regulate extracellular trap formation [ 27 ]. Lysophosphatidylcholines can bind to the G-protein coupled G2A receptors and thereby initiate intracellular signaling and enhance the pro-inflammatory functions of both neutrophils [ 28 ] and monocytes/macrophages [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%